PENINGKATAN MOTORIK HALUS ANAK USIA DINI MELALUI PERMAINAN BUILDING BRICK MARBELE RACE RUN DI TK ARSYAKA KOTA BENGKULU - Lestari, Arini Putri; Pratiwi, Bela Intan; Syaputri, Loren; Apriani, Tesa; Budrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This community service program was conducted at Arsyaka Kindergarten, Bengkulu City, focusing on improving children's fine motor skills through the use of the Building Brick Marbele Race Run game as a learning medium. The program was motivated by the need to optimize fine motor skill stimulation in early childhood while utilizing existing community assets, including a supportive learning environment, enthusiastic students, and active teacher participation in educational game-based learning. The objectives of this program were to describe the implementation of the Building Brick Marbele Race Run game as a learning medium for improving children's fine motor skills and to identify the supporting and inhibiting factors in its implementation. The method used was Asset Based Community Development (ABCD), consisting of the stages of Discovery, Dream, Design, and Destiny. The results showed that the game effectively improved hand-eye coordination, accuracy, concentration, and fine motor skills through activities involving block construction and marble track design. Supporting factors included attractive game design, support from teachers and parents, and a conducive learning environment, while inhibiting factors included limited facilities and differences in children's abilities. The Societal Impact Index (SII) analysis produced an average score of 93.2%, categorized as very good, indicating that the program generated positive social impacts and is feasible for sustainable implementation in early childhood learning activities.